Effects of corticosteroid treatment in patients with severe fever with thrombocytopenia syndrome: A single-center retrospective cohort study - Leiqun Xiong; Ling Xu; Xiaoying Lv; Xin Zheng (International Journal of Infectious Diseases, 2022)
Objectives: To evaluate the effect and safety of corticosteroid (CS) treatment in patients with severe fever with thrombocytopenia syndrome (SFTS). Methods: Patients with and without CS were retrospectively compared by Cox regression and 1:1 propensity score matching analysis to evaluate the effects of CS on mortality and secondary infections in patients with SFTS. Results: A total of 467 patients with SFTS were enrolled in the cohort study, there were 52 fatal cases and 415 nonfatal cases, the overall fatality rate was 11.1%. The mortality was observed in 36/144 (25%) and 16/323 (5%) patients in the CS-treated and non-CS-treated groups, respectively (P < 0.001). Multi variate Cox regression analysis showed that the difference was not statistically significant for CS treatment in fatality (P > 0.05, aHR 0.767, 95% CI 0.360-1.634). Difference in survival time between the CS-treated and non-CS-treated groups after propensity score matching had no statistical significance (Log-rank test P = 0.390), whereas there was a significant difference in secondary infections between the CS-treated and non-CS-treated groups (P = 0.007). Conclusion: Although the CS treatment had no impact on fatality in patients with SFTS, it increased the risk of secondary infections. Administration of CS in patients with SFTS should be carefully considered and evaluated the balance between therapeutic efficacy and adverse effects.